Photocatalytic-induced bubble-propelled isotropic g-C3N4-coated carbon microsphere micromotors for dynamic removal of organic pollutants. Issue 21 (29th April 2022) - Song, Xiaoyi; Tao, Yulian; Liu, Jialiang; Lin, Jian; Dai, Pingqiang; Wang, Qianting; Li, Wei; Chen, Wenzhe; Zheng, Chan
Abstract : An isotropic bubble-propelled g-C3 N4 @CMS micromotor that displays efficient self-propulsion powered by visible light irradiation and offers effective dynamic removal of organic pollutants for environmental applications is described. Abstract : An isotropic bubble-propelled graphitic carbon nitride coated carbon microsphere (g-C3 N4 @CMS) micromotor that displays efficient self-propulsion powered by visible light irradiation and offers effective dynamic removal of organic pollutants for environmental applications is described. Its morphology, structure, and composition were systematically characterized, confirming the successful coating of g-C3 N4 on the CMS surface and a core–shell structure. The photocatalytic-induced bubble propulsion of g-C3 N4 @CMS micromotors essentially stems from the asymmetrical photocatalytic redox reactions of g-C3 N4 on the symmetrical surface of micromotors under visible light illumination. The stacking effect of g-C3 N4 on the CMS surface results in a microporous structure that provides a highly reactive photocatalytic layer, which also leads to effective bubble evolution and propulsion at remarkable speeds of over 167.97 μm s −1 under 250 mW cm −2 visible light in the presence of 30% H2 O2 fuel. The velocity can be easily and effectively adjusted by H2 O2 fuel and the intensity of visible light. Furthermore, the motion state can be reversibly and wirelessly controlled by "switching on/off" light. Such coupling of the high photocatalytic activity of the porous g-C3 N4 shell with the rapid movement of these light-driven micromotors, along with the corresponding fluid dynamics and mixing, result in greatly accelerated organic pollutant degradation. The adsorption kinetics have also been investigated and shown to follow pseudo-second-order kinetics. The strategy proposed here would inspire the designing of light-driven symmetrical micromotors because of the low cost, single component, and simple structure as well as facile and large-scale fabrication, which make them suitable for practical applications.